Analisis Informasi Citra MRI Vertebra Servikal Potongan Axial dengan Penggunaan Flow Compensation antara Pembobotan T2 Sekuens Turbo Spin Echo (TSE) dan gradient echo (GRE) - Ardi Soesilo Wibowo; Ary Kurniawati; Hernastiti Sedya Utami (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: Magnetic Resonance Imaging (MRI) examination of the cervical spine axial slices with T2 weighted flow is often contained artifacts that interfere image result, so it uses flow compensation technique. Axial slices of T2 weighted may use TSE or GRE sequences. This research aims to determine differences in MRI image information of cervical spine axial slices using flow compensation between T2 weighted turbo spin echo (TSE) and gradient echo (GRE) sequences and to get better image information between that both sequences.Methods: This research was a quantitative study with an experimental approach. Data were collected from May to June 2016 in Radiology Installation of Haji Surabaya Hospital using a questionnaire to three respondents. Data were analyzed by statistical tests with SPSS 16 software using Wilcoxon test to determine differences level in image information between T2 weighted TSE and GRE sequences, mean rank value from Wilcoxon test and crosstabulation test to get better image information.Results: There were differences in MRI image information of cervical spine axial slices with using flow compensation between T2 weighted TSE and GRE sequences with p-value was 0.005 (p 0.05). This difference was due to the differences of parameter characteristics between both sequences and T2* GRE was more sensitive to flow to the organ than the TSE. Better MRI image information of cervical spine axial slices using flow compensation was T2* GRE sequence shown by the mean rank 5.50.T2*. GRE was better than T2 TSE because it could show the anatomy of the cervical clearly and informatively, the anatomy of the spinal cord, CSF, neural foramen, intraforaminal structure, corpus vertebrae, disc and the minimum artifacts. While on the anatomy of the facet joint was no significant difference between the TSE and GRE sequences.Conclusion: There were differences in the MRI image information of cervical spine axial slices using flow compensation between T2 weighted TSE and GRE sequences. Better image information was T2* GRE sequence.